Ecological Security Assessment and Countermeasures of Water Environment Based on Improved Analytic Hierarchy Process: A Case Study of Xingtai City - Yuping Li (2019)
© 2019 Peking University. Based on the improved analytic hierarchy process, the authors adopted a 3-scale (0, 1, 2) matrix method to establish regional water ecological security assessment system including 3 layers and 24 indicators according to the real conditions of water environment in Xingtai City. The ecological security assessment system could analyze the influence factors of water environmental security status and evaluate the security situation in Xingtai City. The results showed that the five top influence factors were sewage treatment rate, annual precipitation, wastewater total amount, industrial waste water discharged and urban residential domestic sewage in the 24 indicators. The composite evaluating indexes of the water environment ecological security were within the bandwidth of 0.36 to 0.63, which indicated that the water environment ecological security was still in severe with general or poor state. Some coping strategies and suggestions were put forward to water environmental safety in Xingtai City. The research would provide a theoretical basis for water resource sustainable utilization and a reference for the similar natural condition areas.